Land consolidation reforms: A natural experiment on the economic and political effects of agricultural mechanization - Gabriel Loumeau (ETH Zurich, CER-ETH - Center of Economic Research, 2022)
This paper studies the causal economic and political effects of agricultural mechanization. For identification, it exploits a spatial discontinuity in the intensity of mechanization induced by land consolidation reforms in France between 1945 and 2008. The results suggest that an increase in mechanization leads to long-term growth in population (+9.5%), employment (+15%), and income (+0.5%), but also to an increase in the far-right vote share (+6.1%). To explain the rise in populism despite significant economic growth, the paper shows that mechanization also induces significant immigration flows and changes in social organization (via the decline of the family farm model).
Keywords: D72; O33; Q12; Q15; N54; 330; Mechanization; Natural experiment; Land consolidation; Local activity; Populism